An exploratory investigation into cultural awareness and approach to negotiation of Greek, Russian and British managers - Fraser, Campbell; Zarkada, Anna K. (My University, 2002)
Presents a comparison of approaches to negotiation and level of cultural awareness of international business managers in Russia, Greece and the UK. Demonstrates that although managers in the three countries are distinctly different in their demographic and cultural characteristics they generally exhibit high impression accuracy and adopt a similar approach to the negotiation process. Discusses implications for European business. © 2002, MCB UP Limited
Keywords: Greece; International business; National culture; Negotiating; Russia; United Kingdom